Detection of rabies virus via exciton energy transfer between CdTe quantum dots and Au nanoparticles - Liao, Yan-Juan; Li, Duo-Duo; Cai, Zong-Ling; Cao, Ying; Yu, Dong-Ling; Zhang, Hong-Yun; Kiflu, Abraha Bahlbi; Huang, Zai Yin; Li, Xiao-Ning; Luo, Ting Rong (Frontiers in Veterinary Science, 2022)
Rabies virus belongs to the Lyssavirus of the family Rhabdoviridae and the order Mononegavirales. It is a highly neurotropic virus and causes fatal encephalitis accompanied by severe neurological symptoms in al-most all mammals including humans. Rabies is also an ancient and neglected tropical disease that claims thousands of lives annually in underserved areas of the world including Africa, Asia, and Latin America where vaccination of rabid dogs is in dire need. The diagnosis of the disease depends in large part on the ex-posure history of the victim and clinical manifestations of the disease. Rapid rabies diagnosis is an important step in its prevention and control. Currently, direct fluorescent antibody tests and mouse inoculation tests are considered highly accurate but difficult to use in remote settings. Therefore, for accurate and timely diagno-sis and prevention of rabies, we developed nanomaterials for a novel photoelectrochemical biosensing ap-proach (PBA) for the rapid and reliable diagnosis of rabies virus. This approach uses high-efficiency exciton energy transfer between cadmium telluride quantum dots and Au nanoparticles and is low cost, and easy to miniaturize. By constructing PBA, rabies virus can be detected quickly and with a high degree of sensitivity and specificity; the minimum detection concentration limit for rabies virus is approximately 2.16 ffu/mL of rabies virus particles , or 2.53×101 fg/mL of rabies virus RNA . PBA could also detect rabies virus in the brain and lung tissue from rabid dogs and mice with better sensitivity than RT-PCR.